(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article discusses the advanced foreign experience of increasing competitiveness based on the implementation of a quality system in increasing the competitiveness of enterprises. Also used are a systemic and comprehensive approach, analysis and synthesis, induction and deduction, the method of observing a monographic description, grouping and other methods.